Evaluation of the Efficacy of Intravenous Push and Intravenous Piggyback Ceftriaxone in Critically Ill Patients - Elly R. Sherman; Nha Hue Ta; Trisha N. Branan; Natt Patimavirujh; Luren Ashton Dickinson; Christopher M. Bland; Susan E. Smith (Antibiotics)
Background/Objective: Intravenous fluid shortages have led to fluid-sparing measures such as intravenous push (IVP) administration of antibiotics. This study aimed to compare the safety and efficacy of IVP and intravenous piggyback (IVPB) ceftriaxone in critically ill patients. Results: Demographics were similar in IVP (n = 201) and IVPB (n = 200) groups. Sequential Organ Failure Assessment (SOFA) score was higher, and sepsis and septic shock were more common in the IVP group. Treatment failure occurred in 37.8% of IVP and 19.5% of IVPB groups (p < 0.001). Hospital mortality was more common with IVP (21.4% vs. 9.5%, p < 0.001). Hospital LOS was longer with IVP while intensive care unit (ICU) LOS was similar between the groups. IVP ceftriaxone (OR 2.33, 95% CI 1.43–3.79) and the SOFA score (OR 1.18, 95% CI 1.1–1.27) were associated with treatment failure. Methods: A single-center, retrospective cohort study included adults admitted to an ICU from 2016 to 2021 who received empiric ceftriaxone for ≥72 h. The primary outcome was treatment failure, defined as a composite of inpatient mortality or escalation of antibiotics. Secondary outcomes included length of stay (LOS) and mortality. Chi-squared and independent-sample t-tests were used. Treatment failure was evaluated using multivariate logistic regression. Conclusions: Compared to IVPB, IVP ceftriaxone was associated with higher treatment failure in critically ill patients. Both safety and efficacy should be considered before implementing novel antibiotic administration strategies in practice based primarily on convenience.